Joint manifestations of lyme borreliosis - Herzer, P... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1996)
Muscoloskeletal involvement is a common feature of Lyme Borreliosis. Migratory pain in muscle, joints, or entheses occur early in the illness. Weeks to months later, untreated patients may begin to have intermittent or chronic mono- or oligoarticular arthritis, primarily effecting the knee. Only a small percentage of these patients develop chronic joint involvement. In patients with acrodermatitis chronica atrophicans, distinctive signs of joint and bone involvement can be found beneath the skin lesions.
Keywords: Arthritis, infectious; Diagnosis; Etiology; Lyme disease